Educational Ranking of Rehabilitation Sciences Programs in Iran - Aeen Mohammadi; Rita Mojtahedzadeh; Abdollah Karimi (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: After two decades of nomber expansion of universities of medical sciences and increasing the number of students as one of the most attainable solutions for the problem of substandard status of Iranian community health, recently, the quality-based policies in medical education have taken priority over most of the national health plans. The goal is determine differences in the field of education between schools providing rehabilitation sciences programs in Iran by stratifying their educational services. Materials & Methods: To measure the educational performance of rehabilitation sciences programs nationwide, a benchmarking tool, consisting of aboute 50 indicators, was devised. Their values were defined through consensus developing methods. Each school was asked to introduce a representative who would complete a questionnaire, which was designed to collect schools' information. In the next step, all the divisions were visited by one of the project's members and the school's representative. Then, data retrieval was performed and verified at the project's office. Finally, a special computer software was exploited to perform the final analysis. Results: Schools providing rehabilitation sciences programs were stratified based on their individual scores. Furthermore, all schools were also ranked in each indicator. Among schools providing bachelor's rehabilitation sciences programs, University of Social Welfare and Rehabilitation Sciences gained the first rank, with the score of 73.41 out of 100 Iran Rehabilitation School was the second with the score of 70.91 and Tehran Rehabilitation School gained the third rank with the score of 68.91. Conclusion: This study defines the educational strengths and weaknesses of rehabilitation sciences programs in Iran that could be used as a measure for authorities to devise practical strategies for qualitative and quantitative improvement.